Computer simulations of biotic chiral selection scenarios. Issue 5 (14th October 2022) - Longo, Savino; Mundo, Carmela; Micca Longo, Gaia
Abstract: The biotic scenario of the selection of biological homochirality is one of the most interesting applications of computer modelling to astrobiology. These scenarios have been studied for more than 70 years, yet there are plenty of studies to better assess them, in particular in the development of models of the selective extinction process. In this paper, we review former studies performed by biology-grounded models of this process and present a new class of computer programs: they further demonstrate the complexity of the selective extinction dynamics and the role played into it by non-trivial chemical-physical concepts. Indeed, the results display large and persistent differences between the populations of the two different chiral types, made possible by the freedom of individual populations to fluctuate wildly while the total population is stabilized by the limited availability of chemical energy. Such strong differences ultimately lead to the selective extinction of one of the two types. This way, computer simulations provide increasing evidence in favour of the biotic scenario.